Contemporary Techniques for Freezing Mouse Spermatozoa. Issue 3 (3rd September 2014) - Guan, Mo; Bogani, Debora; Marschall, Susan; Raspa, Marcello; Takeo, Toru; Nakagata, Naomi; Taft, Rob; Fray, Martin
Abstract: Each year, thousands of new mouse models are generated around the world to further biomedical research. Unfortunately, the cost of maintaining mouse colonies makes it uneconomical to keep strains on the shelf that are not part of active research programs. Ideally, these retired strains should be archived. If this is not done and the line is simply killed off, the genetics are lost to future generations of scientists. Traditionally, embryo freezing has been used to cryopreserve mice, but this is expensive, time consuming, requires large numbers of donor females, and usually involves invasive superovulation procedures. Sperm freezing circumvents all of these disadvantages and is rapidly becoming the technique of choice for many repositories. This has been made possible through the use of refined cryoprotective agents and the development of improved in vitro fertilization techniques. This article describes two popular sperm freezing techniques employed by mouse repositories to archive spermatozoa using cryoprotective agents supplemented with either L ‐glutamine or monothioglycerol. Curr. Protoc. Mouse Biol . 4:85‐104 © 2014 by John Wiley & Sons, Inc.